GROWTH PERFORMANCES AND INTESTINAL BACTERIAL POPULATIONS OF PACIFIC WHITE SHRIMP (Penaeus vannamei) FED WITH DIFFERENT DIETARY PREBIOTICS-SUPPLEMENTED FEED - Utami, Diah Ayu Satyari; Wahyu, Wahyu; Insani, Liga; Yudana, I Gusti Putu Gede Rumayasa; Harijono, Teguh (Jurnal Riset Akuakultur, 2024)
Prebiotic applications in aquaculture are mainly given in the form of single or mixed prebiotics. A number of studies compared the effects of different doses or frequencies of a single prebiotic application. However, studies comparing different prebiotics in order to find the most effective ones for certain farmed species are limited. This study aimed to evaluate the effects of different dietary prebiotics on the growth performances and intestinal bacterial populations of Pacific white shrimp (Penaeus vannamei). Four treatments with triplicates were arranged in a completely randomized design (CRD). The treatments consisted of feed supplemented with different dietary prebiotics for Pacific white shrimp, including control (without dietary prebiotic), 0.5% honey (v/w), 0.5% mannan-oligosaccharide (MOS) (w/w), and 0.5% inulin (w/w). Pacific white shrimp (1.59 ± 0.12 g) were randomly stocked in 12 glass tanks (60 x 30 x 40 cm3) with a stocking density of 15 shrimp per tank. The shrimp were fed the experimental feed to apparent satiation four times daily for 30 days. Growth parameters observed consisted of final weight, specific growth rate (SGR), feed conversion ratio (FCR), survival of Pacific white shrimp, total bacterial count, total Vibrio count, and dominance of Vibrio in the intestine of experimental shrimp. Dietary prebiotics improve the growth performances of Pacific white shrimp. The highest growth performances were found in the shrimp treated with dietary honey. The improvement in growth performance may be due to the ability of honey to boost the proliferation of beneficial bacteria in the intestines of Pacific white shrimp.Pemanfaatan prebiotik dibagi menjadi dua kelompok yang terdiri atas prebiotik tunggal dan prebiotik campuran. Banyak penelitian sebelumnya yang berfokus pada perbandingan dosis atau frekuensi satu jenis prebiotik tetapi tidak membandingkan jenis prebiotik yang berbeda untuk menemukan prebiotik yang paling efektif untuk spesies tertentu. Penelitian ini bertujuan untuk mengevaluasi pengaruh pemberian pakan prebiotik yang berbeda terhadap kinerja pertumbuhan dan populasi bakteri usus udang vaname (Penaeus vannamei). Penelitian ini dilakukan melalui rancangan acak lengkap (RAL) dengan empat perlakuan dan tiga ulangan. Perlakuan yang diberikan dalam penelitian ini terdiri atas pemberian pakan prebiotik yang berbeda pada udang vaname meliputi kontrol (tanpa prebiotik), madu 0,5% (v/b), mannan-oligosakarida (MOS) 0,5% (b/b), dan inulin 0,5% (b/b). Udang vaname (1,59 ± 0,12 g) ditebar secara acak dalam 12 akuarium kaca (60 x 30 x 40 cm3) dengan padat tebar 15 udang per akuarium. Udang diberi pakan percobaan sampai kenyang empat kali sehari selama 30 hari. Parameter yang diamati terdiri atas bobot akhir, laju pertumbuhan spesifik (LPS), rasio konversi pakan (RKP), kelangsungan hidup udang vaname, jumlah bakteri total, jumlah Vibrio total, dan dominasi Vibrio dalam usus udang percobaan. Pemberian pakan prebiotik meningkatkan kinerja pertumbuhan udang vaname. Kinerja pertumbuhan tertinggi ditemukan pada udang yang diberi madu. Peningkatan kinerja pertumbuhan ini mungkin disebabkan oleh kemampuan madu dalam meningkatkan perkembangbiakan bakteri menguntungkan di usus udang vaname.